Злое солнце: [роман] / Александр Щелоков - Щелоков Александр Александрович (Солдаты удачи, 2007)
Экземпляры: ф.6 (20161019) / Инвентарный номер: 1883 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Щ 46 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44